In vitro Gas Production of Sorghum-Indigofera Forage-Based Complete Feed for Ruminants. Issue 1 (1st April 2022) - Somanjaya, R; Imanudin, O; Turohman, S M; Fuah, A M; Rahayu, S; Abdullah, L; Setiadi, M A
Abstract: Making a palatable complete feed formulation has a good effect on ruminant productivity, and eco-friendly feed is a solution step in sustainable livestock production. The aims of this study were to evaluate the quality of complete feed based on forage sorghum-Indigofera on the in-vitro of gas production and nutrient digestibility value. Three feed compositions consisting of forage silage of sorghum, Indigofera hay, and rice bran were mixed as SI feed and field grass (FG) as control. All the experimental feeds were replicated five times, then gas production and nutrient digestibility were tested in in-vitro. Data were analyzed with ANOVA and further tested using Duncan's multiple range test (DMRT). The results showed that the complete feed composition SI2 and SI3 lower N-NH3 (p<0.05) than SI1 and FG. Meanwhile, the VFA content increased (p<0.05) along with the Indigofera hay. The value of pH and the number of gas production from the feed did not differ. All SI complete feed compositions had better nutrient digestibility values (p<0.05) than FG. It can be concluded that complete feed based on forage sorghum-Indigofera is an eco-friendly feed because it can reduce N-NH3 gas and total gas production without reducing the digestibility value of feed nutrients.